RISIKO JANGKA PANJANG FISKAL DOMINANCE TERHADAP STABILITAS MONETER DAN UTANG PUBLIK INDONESIA - Aufa Zidan Nul Arifin rifin; Sarpini (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
Fiscal dominance occurs when government fiscal policy dominates monetary policy, which can threaten monetary stability and increase public debt risk (Sargent & Wallace, 1981). This study analyzes the long-term risks of fiscal dominance in Indonesia, focusing on its impact on inflation, interest rates, and public debt accumulation. Using historical data from Bank Indonesia and the Ministry of Finance for the period 2000–2022, regression analysis and scenario simulations show that fiscal dominance increases the risk of chronic inflation and attracts public debt of up to 80% of GDP in extreme scenarios (Cochrane, 2011; oo IMF, 2021). In conclusion, there is a pressing need for stronger fiscal-monetary policy coordination to maintain Indonesia's economic stability (Siregar & Goo, 2008)